PERSEPSI MASYARAKAT TERHADAP PELAYANAN PUBLIK BERBASIS APLIKASI PEKANBARU DALAM GENGGAMAN - rika rahim (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2022)
Services are increasingly developing times experiencing changes from service, it is undeniable that public services known in government are electronic-based services (Electronic Government), one of which is the Pekanbaru government through the Pekanbaru statistical informatics communication service and coding, namely the Pekanbaru application in hand. Of course, after the community uses the application, it gives rise to several perceptions or assessments which are one of the factors in the description of how the service that is felt or obtained by the community through the Pekanbaru application is in the grip of whether it is in accordance with service users. This study aims to determine and explain the public's perception of public services based on the Pekanbaru application in hand. The theory used by the author in this study is a theory about the dimensions of public services, service is one of the rights that must be obtained by the community. This study uses a quantitative descriptive research, with data collection techniques, namely questionnaires, to the community using the Pekanbaru application in hand with a sample of 99 respondents determined through incidental sampling technique, for data processing the questionnaire test is carried out using a product and service solution statistical program. (SPSS) windows version 25. Test the validity of the instrument using product moment correlation and reliability test using Cronbach's alpha. The results of each of the indicators are usability (usability) worth 61.09% or good, information quality indicators (information quality) 78.75% or good, Service Interaction Quality indicators (Service Interaction Quality) 80.11% or good, and overall indicators (overall) 81.21% or very good so that the results obtained are 75.04% categorized as good.